1998
DOI: 10.1038/35087
|View full text |Cite
|
Sign up to set email alerts
|

Detection of intergalactic red-giant-branch stars in the Virgo cluster

Abstract: It has been suspected for nearly 50 years that clusters of galaxies contain a population of intergalactic stars, ripped from galaxies during cluster formation or when the galaxies' orbits take them through the cluster center. Support for the existence of such a population of free-floating stars comes from measurements of the diffuse light in clusters, and from recent detections of planetary nebulae with positions and/or velocities far removed from any observed cluster galaxy. But estimates for the mass of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
142
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(152 citation statements)
references
References 27 publications
9
142
0
1
Order By: Relevance
“…As we have previously noted, A1553 lies behind the Virgo Cluster, which is known to have intracluster light of its own (Arnaboldi et al 1996;Feldmeier et al 1998;Ferguson et al 1998;Durrell et al 2002). Does the presence of this foreground intracluster light affect our measurements of the ICL of A1553?…”
Section: A1553 and Virgo's Iclmentioning
confidence: 96%
“…As we have previously noted, A1553 lies behind the Virgo Cluster, which is known to have intracluster light of its own (Arnaboldi et al 1996;Feldmeier et al 1998;Ferguson et al 1998;Durrell et al 2002). Does the presence of this foreground intracluster light affect our measurements of the ICL of A1553?…”
Section: A1553 and Virgo's Iclmentioning
confidence: 96%
“…In favor of the existence of intergalactic material, Theuns & Warren (1997), Mendez et al (1997), andCiardullo et al (1998) presented evidence for the presence of intergalactic planetary nebulae within the Fornax and Virgo Clusters, while Ferguson et al (1998) reported several hundreds of intracluster red giants in Virgo. Some globular clusters may have been stripped with them from other cluster galaxies if this is their origin (Harris 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In the last twenty years, the presence of intra-cluster starlight (ICL) has been inferred from surface brightness measurements (Bernstein et al 1995) and from the detection of individual extragalactic stars (Ferguson et al 1998), planetary nebulae (Arnaboldi et al 1996), and HII regions (Gerhard et al 2002). The study of ICL and its origin could shed light on the evolution of galaxies in clusters, a complex process involving various mechanism such as tidal interactions (Gnedin 2003), galaxy harassment (Moore et al 1996) and ram pressure (Gunn & Gott 1972).…”
Section: Introductionmentioning
confidence: 99%